Hemiarthroplasty as a salvage treatment for failed reverse total shoulder arthroplasty - Philipp Kriechling, MD; Octavian Andronic, MD; Karl Wieser, MD (JSES International, 2021)
Background: The implantation rates of reverse total shoulder arthroplasties (RTSAs) are increasing worldwide, resulting in higher absolute numbers of the associated complications and revision surgeries. This requires the discussion of salvage therapies for failed RTSAs without revision to a new RTSA. Revision to hemiarthroplasty may offer a valid fallback option in certain cases. This study aimed to analyze the incidence, indications, and clinical outcomes, especially the reduction in pain levels compared to a matched control group. Methods: Our prospectively enrolled patient cohort of RTSA implantations at a tertiary referral center between January 2005 and December 2018 was retrospectively queried for revision to a hemiarthroplasty. For clinical outcome evaluation, a minimum follow-up duration of 2 years after revision to hemiarthroplasty was required. Clinical outcome measures were compared to two matching groups, one with RTSA preserving revision and one without any reintervention. The outcome measures were the absolute and relative Constant-Murley score (aCS and rCS), Subjective Shoulder Value (SSV), range of motion, and pain. Results: A total of 21 out of 1237 RTSAs (1.7%) underwent salvage revision to hemiarthroplasty at a mean time of 20 ± 21 months (range, 1-75 months). Of those, 12 were available for a minimum follow-up of 2 years after revision to a hemiarthroplasty. The main indications were glenoid loosening (8/12), scapular spine fracture (2/12), and instability (2/21). Clinical outcome was analyzed at a mean follow-up period of 46 ± 26 months (24 months to 123 months) after revision to a hemiarthroplasty. The revision significantly reduced CS pain from 6 ± 4 points to 12 ± 3 points (scale 0 to 15 with 15 as optimum, P < .01). The aCS, rCS, SSV, and range of motion did not improve. Comparison with the RTSA preserving revision group and the RTSA group without reintervention showed significantly worse outcome scores for aCS (33 ± 10 vs. 55 ± 19 vs. 69 ± 12 points), rCS (41 ± 14% vs. 67 ± 20% vs. 84 ± 13%), SSV (35 ± 19% vs. 64 ± 20% vs. 81 ± 15%), flexion (53 ± 27° vs. 64 ± 20° vs. 128 ± 24°), and abduction (50 ± 23° vs. 109 ± 42° vs. 142 ± 24°). Pain was similar in all groups at the last follow-up visit. Conclusion: In a few cases, RTSA retention or revision to another RTSA is impossible. For those patients, conversion to hemiarthroplasty is a valid fallback option to reduce the patient's pain levels and provide low-level function.